PENGARUH ELECTRONIC WORD OF MOUTH PADA FORUM ONLINE FEMALE DAILY TERHADAP MINAT BELI PRODUK PURBASARI DI KALANGAN REMAJA WANITA - Annisa Kesuma Wardani; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Electronic Word of Mouth becomes a vanue or a place that is very important for consumers to give their opinions and is considered more effective than word of mouth because of the level of accessibility and wider range than traditional word of mouth offline. In communication theory using computer intermediaries or usually called Computer Mediated Communication theory examines how human behavior is maintained and changed by exchanging information through machines This study aims to find out how much influence the electronic word of mouth on the online forum Female Daily to the decision of purchasing Purbasari products among women.This research uses explanatory quantitative research method. Data collection was done by distributing questionnaires to 200 respondents of the online forum Female online online who have used matte lipstick Purbasari. Data analysis using simple linear regression on SPSS 23 for windows program.The result of the research shows the influence of electronic word of mouth with indicator of Platform Assistancel, Concern for Other, Expressing Positive Emotions, Advice Seeking, and Venting Negative Feeling on Female Daily online forum to purchase decision with Stability indicator on Product, Habit in Buying Product, Recommendations to Others and Repurchase Purbasari products among young women. This can be seen from the coefficient value in the research that is Y = 2.487 + 0.837 X. The coefficient of determination (Rsquare) is 0.643, meaning the contribution of electronic word of mouth influence to the purchase decision is 64.3% with strong category. While the rest of 35.7% influenced by other variables. The highest indicator of the Venting Negative Feeling indicator of the electronic word of mouth variables amounted to 146 or 73 percent. While the lowest indicator is the Stability indicator on a product of the purchase decision variable as much as 86 or 43 percent.Keywords: Electronic Word of Mouth, Purchase Decision